Developing and Validating a Culturally-Based Career Search Efficacy Scale for Vocational School Students in Aceh - Asriyana, Asriyana; Sugiharto, DYP; Sunawan, Sunawan; Mugiarso, Heru (KONSELOR, 2025)
This study aimed to develop and validate a culturally grounded Career Search Self-Efficacy (CSSE) scale for Acehnese vocational students. Using a sequential exploratory mixed-methods design, the qualitative phase elicited culturally relevant indicators through interviews with students and counselors and a focus group discussion, resulting in 91 preliminary items. These included culturally grounded dimensions such as parental blessing and family deliberation (musyawarah), seeking jobs consistent with Islamic (halal) values, and Acehnese etiquette in communication (e.g., greeting with Assalamu’alaikum). Expert review by specialists in measurement, counseling, and Acehnese culture refined the items for clarity, representativeness, and cultural appropriateness. The quantitative phase involved 1,307 students from vocational schools in Banda Aceh, divided into subsamples for exploratory factor analysis (EFA, n = 579) and confirmatory factor analysis (CFA, n = 728). EFA yielded a five-factor solution Networking Efficacy, Career Exploration Efficacy, Interview Efficacy, Personal Exploration Efficacy, and Family Support which explained 41.7% of the variance. CFA confirmed the five-dimension structure with acceptable-to-good fit indices (CFI = .934, TLI = .923, IFI = .953, GFI = 0.942; RMSEA = .045; SRMR = .042; NFI = .884). Convergent validity was borderline (AVE ≈ .35–.50) but supported by significant loadings and composite reliability, while discriminant validity was satisfied. Reliability was acceptable overall (α = 0.822, ω = 0.817), though Interview and Personal Exploration were slightly below .70. Criterion validity was supported through positive correlations with Career Decision Self-Efficacy (CDSE-SF) and Student Life Satisfaction (SLSS), with Family Support showing the strongest associations. Theoretically, the results extend CSSE and Social Cognitive Career Theory (SCCT) by identifying Family Support as an independent efficacy domain in a collectivist setting. Practically, the Aceh-Based CSSE Scale provides school counselors with a diagnostic tool for culturally responsive career interventions that integrate family and community supports.